A novel approach to the design of a needle driver with multiple DOFs for pediatric laparoscopic surgery. Issue 1 (February 2013) - Fujii, Masahiro; Sugita, Naohiko; Ishimaru, Tetsuya; Iwanaka, Tadashi; Mitsuishi, Mamoru
Abstract Introduction: The objective of our research was to design and develop a novel needle driver with multiple degrees of freedom (DOFs) for pediatric laparoscopic surgery. Pediatric laparoscopic surgery has many advantages for patients, but the difficulty of the operation is increased due to many restrictions. For example, the motion of the needle driver is restricted by the insertion points, and the operation workspace is smaller in children than in adults. Material and methods: A needle driver with 3 DOFs and a 3.5-mm diameter is proposed and implemented in this study. Grasping DOF is achieved using a piston mechanism actuated by a wire. Deflection and rotation DOFs are actuated by gears. Results: Experiments were conducted to evaluate the workspace and ligation force, and the results confirmed that the needle driver meets all the necessary requirements. Finally, a first reaction of a pediatric surgeon on the suturing and ligaturing capabilities of the prototype is reported. Conclusion: A multi-DOF needle driver with a new mechanism was proposed for pediatric laparoscopic surgery and a first prototype was developed. It is expected that further elaboration of the developed first prototype of the needle driver may contribute to the advancement of pediatric laparoscopic surgery.